Characterization of speciated aerosol direct radiative forcing over California. Issue 5 (7th March 2013) - Zhao, Chun; Ruby Leung, L.; Easter, Richard; Hand, Jenny; Avise, Jeremy
Abstract: [1] The WRF‐Chem model, with the added capability of diagnosing the direct radiative forcing of individual aerosol species, is used to characterize the spatial and seasonal distribution of speciated aerosol direct radiative forcing over California. Overall, the simulation in 2005 is able to reproduce the observed spatial and seasonal distribution of total PM2.5 mass concentration and the relative contribution from individual aerosol species. On statewide average over California, all aerosol species reduce the surface net radiation fluxes, with a total by about 1.5 W m −2 (winter minimum) to 3 W m −2 (summer maximum). Elemental carbon (EC) is the largest contributor in summer (−1.1 W m −2 and ~35%), and sulfate is the largest in winter (−0.45 W m −2 and ~30%). In the atmosphere, total aerosol introduces a warming effect of about 0.5 W m −2 (winter minimum) to 2 W m −2 (summer maximum). EC and dust contribute about 75 − 95% and 1 − 10% of the total warming through the seasons, respectively. At the top of the atmosphere (TOA), the overall total aerosol direct radiative effect is cooling of −1.0 W m −2 through the seasons, with sulfate as the biggest contributor of −0.4 W m −2 (winter minimum) to −0.7 W m −2 (summer maximum). EC produces a TOA warming of up to about 0.7 W m −2, whereas all other aerosol species produce a TOA cooling. The diagnostic method implemented in WRF‐Chem can be applied to other regions to understand the roles of different aerosols in the direct radiative forcing and regional climate. Abstract : Key Points Evaluate model performance with various meteorological and aerosol measurements Understand seasonal and spatial variation of speciated aerosols over California Diagnose direct radiative forcings for individual aerosol species